The Meaning and Essence of the Concept of National Currency - Abrorjon Habibullayev Ahmadali’s son (Miasto Przyszłości, 2023)
Currency (Italian "valuta", Latin "valere" - value, value) – 1. The currency of the country and its type (gold, silver, paper); 2. Currencies of foreign countries used in international transactions, as well as credit and payment documents (bills, checks, banknotes, etc.) expressed in the currency of these countries and used in international settlements. Until the 19th century, silver currency or bimetallism monetary system was widespread in most countries. From the 19th century, first in England, then in other countries, gold currency began to be used. Since the 70s of the 20th century, paper currency, that is, banknotes and paper money that cannot be exchanged for gold and silver, has appeared. They are exposed to inflation and depreciate, as a result of which the state conducts devaluation measures.